Antecedents of smart tourism destination perceived attractiveness and behavioral intention for digital natives - Lastaripar Goeltom, Andar Danova; Hurriyati, Ratih; Gaffar, Vanessa; Wibowo, Lili Adi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In order to achieve high levels of satisfaction from the digital native generation, tourism destinations must adapt to how they interact and present content that matches their technological preferences. This study aims to measure the perception of STD attractiveness for digital natives by exploring antecedent factors and their impact on intentional behavior. This study uses a quantitative approach. The data was collected by distributing online questionnaires with sample aged 18 to 41 years who have traveled by involving the process of transactions, bookings, and searching for information digitally in the last 1 year. 318 responses were collected that were considered adequate for further processing in the analysis process. Measurements were made using the SEM-PLS technique. The study has found that digital natives view of interactivity and digital security can influence their assessment of STD attractiveness. This study model partially explains some of the factors that make up STD values and their relationship to intentional behavior. This study can consider strategies for strengthening digital interaction and security in the context of STDs for DMOs to build the attractiveness of destinations to attract tourist visits. This study provides a more specialized perspective by focusing on assessing digital natives as the main opinion.